Decision Support System for the Selection of Prospective Recipients of Poor Student Assistance with Comparison of ROC-WASPAS and ENTROPY-WASPAS - Theodora, Rahel Rizki (Devitara Innovations, 2024)
The process of selecting potential recipients of aid for poor students often experiences difficulties because it involves many criteria that must be assessed accurately and objectively. Mistakes in assessment can result in the distribution of aid not being on target, thereby harming those who should receive the aid. This research aims to develop a decision support system that can assist in selecting potential recipients of aid for poor students by comparing two different ranking methods, namely ROC-WASPAS and ENTROPY-WASPAS. The ROC-WASPAS method combines the Rank Order Centroid (ROC) technique to determine criteria weights with the Weighted Aggregated Sum Product Assessment (WASPAS) for ranking alternatives. In contrast, the ENTROPY-WASPAS method uses entropy to determine criteria weights based on the level of data uncertainty, combined with the WASPAS method. The aim of this research is to compare the effectiveness of the two methods in producing accurate and fair rankings for potential aid recipients. The contribution of this research includes the development of a reliable evaluation model and the provision of a system that makes it easier for decision makers to select aid recipients more precisely. Results Comparison between the ROC-WASPAS and Entropy-WASPAS evaluation methods shows that both can produce different rankings for the same alternative. This shows the importance of choosing evaluation methods carefully in decision making, because the final results can be influenced by the approach used. This variation in ratings indicates that each method has a unique approach to assessing performance, and a deep understanding of the method used is necessary to provide a more comprehensive picture.